Young Adults and Allergic Rhinitis: A Population Often Overlooked but in Need of Targeted Help - Georgina Jones; Rachel House; Sinthia Bosnic-Anticevich; Lynn Cheong; Biljana Cvetkovski (Allergies)
Allergic Rhinitis (AR) currently affects 27% of young adults (18–24 years old) in Australia. Although the nature of AR and its management are well-researched in adult and paediatric populations, little is known about young adults. Given the biopsychosocial developmental challenges faced by young adults, this study aims to investigate young adults’ AR management and the source of its influence. A total of 185 young adults with AR in Australia completed an online survey. Seventy-eight percent were female and had a mean age of 21.9 years old. The majority (99%) had moderate to severe symptoms and affected at least one aspect of their quality of life (97%). Despite this, only 11% of participants were using appropriate medications. Parents (50%) were the most common influencer in young adults’ medication use, and general practitioners were most commonly sought for information (63%) and advice (70%). Young adults do not manage their AR with appropriate medications despite consulting healthcare providers, and this was reflected in the heavy burden reported on their quality of life. This study bridges our gap in understanding and shows that young adults lack developmentally appropriate support to equip them with the health literacy skills required to transition into adult healthcare.